Biology of Obesity: Lessons from Animal Models of Obesity. (5th January 2011) - Kanasaki, Keizo; Koya, Daisuke
Abstract : Obesity is an epidemic problem in the world and is associated with several health problems, including diabetes, cardiovascular disease, respiratory failure, muscle weakness, and cancer. The precise molecular mechanisms by which obesity induces these health problems are not yet clear. To better understand the pathomechanisms of human disease, good animal models are essential. In this paper, we will analyze animal models of obesity and their use in the research of obesity-associated human health conditions and diseases such as diabetes, cancer, and obstructive sleep apnea syndrome.